The Current State of Data to Estimate Prevalence and Severity of Food Allergies in the United States - Juliana M. Ruzante; Caroline Rains; Catherine Viator; Dan Liao; Darryl Creel; Stefano Luccioli; Gabriella Anic; Beverly J. Wolpert; Christopher Warren; Laura DiGrande (Journal of Food Protection)
Currently, in the United States, there is no comprehensive surveillance system to collect data on food allergies; however, prevalence and severity data are critical to quantify the burden of food allergies, develop evidence-based control measures, detect emerging issues, and monitor trends. To address this gap, we conducted a literature search, and expert interviews to identify surveillance systems and datasets that could be used to estimate the prevalence and severity of food allergies in the United States overall and for specific foods. Inclusion and exclusion criteria were developed and used to screen each data source. Selected articles were evaluated according to quality parameters to identify the most appropriate studies. Most studies estimated the prevalence of food allergies in children, investigated multiple foods, and used surveys to collect self-reported data. Despite the high quality, robust study designs, and comprehensive survey instruments that currently exist, the studies identified do not provide sufficiently recent data to estimate the current burden of food allergies in the country. Studies lack consistencies across the years making the analysis of trends over time a challenge. National surveys conducted by Northwestern University in 2009/2010 and 2015/2016 represented the best available data; however, these data are likely outdated and are limited in assessing temporal food allergy trends. Data to accurately estimate the current prevalence and severity of food allergies and related trends are lacking. U.S. public health agencies should explore the development of a comprehensive surveillance program to address this gap and help inform evidence-based policies in food allergy management and prevention.